Stability analysis for yield and productivity traits in rabi sorghum (Sorghum bicolor) under protective irrigation - Tembhurne, B V; Kuchanur, P H; Biradar, B D (The Indian Journal of Agricultural Sciences, 2012)
The phenotypic stability of nine sorghum [Sorghum bicolor (L.) Moench] genotypes was studied for grain yield and productivity traits during 2004, 2005 and 2006. Analysis of variance revealed significant differences among the environments indicating adequate heterogeneity of environments and their suitability for evaluating the genotypes. The mean sum of squares for genotypes were also significant for days to 50% flowering, 100-seed weight, grain yield/plant, fodder yield/ha and harvest index revealing genetic variability among genotypes for these traits. The genotype × environment interactions for grain yield and other characters was significant and the significant mean square due to environment (linear) indicated the existence of real varietal differences in characters for regression over the environmental mean. Among the genotypes, SVD 0107 produced the highest mean yield (3 569.80 kg/ha) followed by JP1-1-5 (3 491.60 kg/ha). Considering all the stability parameters, SVD 0107 and JP 1-1-5 exhibited above average stability and DSV 4 registered below average stability for grain yield/ha. Genotype JP1-1-5 showed above average stability for grain yield/ha and wider stability for fodder yield/ha hence, it can be exploited for both grain and fodder purpose.